Integrating liveworksheets for multirepresentational probability learning: A study on design validity and instructional effectiveness. - Widyawati, Santi; Putra, Fredi Ganda; Bekti, Mutiara Fitria (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
Mathematical representation is essential for students’ understanding, especially in probability which requires visual symbolic and verbal interpretation. However many digital worksheets lack integration across these modes. This study aimed to develop and evaluate a multirepresentational electronic worksheet using the Liveworksheets platform to enhance students’ representational skills in probability. The study applied the ADDIE development model which included curriculum analysis expert validation and classroom implementation through a pretest and posttest design. The worksheet combined interactive charts symbolic equations and explanatory prompts into a unified learning experience. Panels of experts consisting of subject-matter specialists media experts and psychometricians validated the content usability and alignment with educational objectives. Students who participated in pilot activities responded positively and reported high levels of engagement. The pretest and posttest results demonstrated improvements in students’ visual symbolic and verbal representation skills. These outcomes indicate that integrating multiple representation modes into a digital learning tool can effectively support deeper conceptual understanding. The study concludes that the developed worksheet is educationally valid engaging for learners and practical for classroom use. It offers a promising approach to support differentiated instruction in mathematics and enrich students’ learning experiences particularly in mastering abstract probability concepts.